Test Performance Study on qPCR Assays for Detection of Phyllosticta citricarpa - Tjaša Jakomin; Janja Zajc Žunič; Polona Kogovšek (Pathogens)
Citrus black spot (CBS), caused by the fungus Phyllosticta citricarpa, significantly affects citrus fruit marketability and can lead to premature fruit drop. Accurate and reliable detection of this quarantine pathogen is crucial, particularly for asymptomatic plant material. This study evaluated two qPCR assays, the EPPO recommended assay PC and assay Pc-TEF1, based on TEF region, for detecting P. citricarpa through a collaborative test performance study (TPS). DNA from the isolates of Phyllosticta spp. and other fungi was spiked into citrus fruit peel extracts (lemon, orange, and pomelo) and distributed among 13 laboratories. Sample and qPCR assay stability under typical transport conditions was confirmed, although prolonged storage affected Pc-TEF1 assay performance. The assays were assessed based on sensitivity, specificity, reproducibility, and repeatability. Both assays demonstrated high performance, with repeatability and reproducibility exceeding 95%. The PC assay, as expected, detected different related Phyllosticta species, while Pc-TEF1 showed higher specificity for P. citricarpa included in the TPS alone. Additionally, inhibitory effects were observed specifically in the pomelo peel samples, suggesting matrix-dependent variability. This TPS confirms that both PC and Pc-TEF1 qPCR assays are robust. Further evaluation of the qPCR assays would support the selection of the most reliable assays for the detection of P. citricarpa, contributing to the effective management of CBS disease in citrus production and trade.